Managing Workflow Processes through Access Control Policies - Fard, Rasool Esmaeily; Klein, Alan; Nezhad, Reza Karimi (INFOCOMP Journal of Computer Science, 2010)
Workflow systems enable organizations to model and execute business processes, but the majority of contemporary workflow management systems are not designed and suited for supporting dynamic business processes. One of the deficiencies is the inability to model realistically the organization of an enterprise to manage the dynamic human-centric business processes. An access control architecture for managing workflow processes is described in the paper. It includes an organizational model and an authorization model for supporting dynamic business processes. More specifically, authorization policies are expressed in an SQL-like language which can be easily rewritten into query sentences for execution. In addition, the architecture supports dynamic integration and execution of multiple access control policies from disparate enterprise resources. Finally, a prototype implementation of the dynamic business process management architecture is described